2020
DOI: 10.17707/agricultforest.66.1.24
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Possibilities of Reducing the Quantity of Mineral Fertilizer Application Using Different Types of Organic Fertilizers in Cardinal Grape Variety

Abstract: This paper presents the results of a three-year study (2010-2012) on the influence of different types and combinations of fertilisers on the agro-biological, economic and technological characteristics of the Cardinal variety of grapes. The study was carried out in the experimental vineyard of the Biotechnical Faculty in Podgorica to explore the possibility of reducing the use of mineral fertilisers by applying various organic fertiliser sources. Ten variants of fertilisation were applied: control (500 kg ha-1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…The acid content in the must is an important indicator of the quality of grapes, because the taste and harmony of grapes and produced wine depends on their presence (Popović, 2020). The results of two -year study demonstrated that the average acid content in must was satisfactory and characteristic for Žižak variety grown in agroecological conditions of Podgorica vineyard area.…”
Section: Climate Conditionsmentioning
confidence: 94%
“…The acid content in the must is an important indicator of the quality of grapes, because the taste and harmony of grapes and produced wine depends on their presence (Popović, 2020). The results of two -year study demonstrated that the average acid content in must was satisfactory and characteristic for Žižak variety grown in agroecological conditions of Podgorica vineyard area.…”
Section: Climate Conditionsmentioning
confidence: 94%
“…However, several studies confirmed that the combined application of mineral and organic fertilizers give the best results in terms of grape yield (4.7 kg vine⁻ 1 ) and the physical and chemical characteristics of bunches and berries (14.72% sugar) [70,71]. Only individual application of organic fertilizers led to the lower yield (3.6 kg vine⁻ 1 ) [70,72] and lower content of sugar in berries (14.29%) [70,73], as well as to the increase in berry acidity (4.32 g L⁻ 1 ) [70]. The overall polyphenol concentration is higher in organic grapes, resulting in a higher protection from oxidation [72].…”
Section: Effect Of Fertilization Strategies On Soc Concentrationmentioning
confidence: 99%
“…The lack of potassium is manifested by lower yields and quality of the tubers produced. Poor potassium nutrition also causes a decrease in specific gravity [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…The positive effect of manure is also reflected in the increase of the humus component of the soil and the faster warming of the soil in early spring, when higher temperatures are needed for the growth and development of the tuber sprouts. Through its mineralization, plant nutrients and carbon dioxide are released, essential substances in the process of photosynthesis [21,22]. In addition, the released CO 2 contributes to the activation of nutrients from the existing land reservoir, increasing their accessibility to plants [23].…”
Section: Introductionmentioning
confidence: 99%